2018
DOI: 10.1108/jeee-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Chinese entrepreneurship attributes: a comparative GEM data analysis

Abstract: Purpose The purpose of this paper is to compare influential factors of entrepreneurial activities over time in China and to compare China with other selected countries. The data are collected from Global Entrepreneurship Monitor (GEM). The method used is decision trees and chi-square automatic interaction detector (CHAID) analysis, which isolates important factors and examines entrepreneurship predictor importance. Design/methodology/approach The method used is decision trees and CHAID analysis which isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Furthermore, local governments can play an essential role in entrepreneurship and regional development (Liu and Huang 2018). The number of research on temporal context is modest and focuses on two separate themes, namely changing role of guanxi (Guo and Miller 2010;Peng, Duysters, and Sadowski 2016;Burt and Opper 2017;Liu et al 2018c) and dynamics of entrepreneurial emergence (Atherton and Newman 2016;Cinar, Du, and Hienkel 2018;Dai, Wang, and Liu 2019). Du et al's (2018) recent research on emergence of the digital entrepreneurial ecosystem captures the impact of Internet revolution on entrepreneurship in China.…”
Section: An Overview Of Approaches To Contextualization In Chinese Entrepreneurship Researchmentioning
confidence: 99%
“…Furthermore, local governments can play an essential role in entrepreneurship and regional development (Liu and Huang 2018). The number of research on temporal context is modest and focuses on two separate themes, namely changing role of guanxi (Guo and Miller 2010;Peng, Duysters, and Sadowski 2016;Burt and Opper 2017;Liu et al 2018c) and dynamics of entrepreneurial emergence (Atherton and Newman 2016;Cinar, Du, and Hienkel 2018;Dai, Wang, and Liu 2019). Du et al's (2018) recent research on emergence of the digital entrepreneurial ecosystem captures the impact of Internet revolution on entrepreneurship in China.…”
Section: An Overview Of Approaches To Contextualization In Chinese Entrepreneurship Researchmentioning
confidence: 99%
“…Similarly, Cinar et al (2018) suggested that the enhancement of ’ entrepreneurs’ human capital through skill and knowledge education and training is critical to support ’ China’s entrepreneurial growth. Unger et al (2011) evidenced a significant but small relationship between human capital and entrepreneurial success.…”
Section: Resultsmentioning
confidence: 99%
“…In the Chinese entrepreneurial context, small and medium enterprises comprise the majority of the Chinese economy, accounting for 58.5% of GDP in 2009 ( Zhou, 2012 ). Chinese entrepreneurs are mainly driven by profit and commercial value within the ambiguous rules and limited institutional framework of business governance in China ( Cinar et al, 2018 ). Accordingly, Darwinian social identity dominates the Chinese entrepreneurs’ mentality ( Kong, 2017 ; Su et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%